The IMF and the World Bank : How Do They Differ? - Driscoll, David (Pamphlet Series; Pamphlet Series, No., 1995)
This paper discusses how the IMF and the World Bank differ from each other. The IMF is small and, unlike the World Bank, has no affiliates or subsidiaries. Most IMF staff members work at headquarters in Washington, D.C., although three small offices are maintained in Paris, Geneva, and at the United Nations in New York. Its professional staff members are for the most part economists and financial experts. The World Bank is an investment bank, intermediating between investors and recipients, borrowing from the one and lending to the other. The structure of the World Bank is somewhat more complex compared with the IMF.